El sistema nacional no-jurisdiccional de defensa de los derechos humanos algunas preocupaciones - Carpizo, Jorge (Anuario de Derechos Humanos. Nueva Época, 2009)
This essay states how the figure of the Mexican Ombudsman was created and how, in 1992, when it was carried on to constitutional level, a national non-jurisdictional protection system was developed to protect human rights, with its own peculiarities as the existence of a Consultive Council. It was a renewed or transformed Ombusdman. Also, there are reported the main problems that obstruct this national system from performing adequately nowadays. We submit some suggestions to solve them.
Keywords: Domestic Ombudsman; Non-jurisdictional protection system of human rights; National Council for Human Rights; Recommendations; Consultive Councils; Non-governamental organizations (NGO)